The Disruption of Islamic Culture for Youth through the Korean Wave (Case Study of Social Media, Tik Tok) - Miftakurjana, Inka (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The Korean Wave or Hallyu phenomenon has become a global concern in recent years in the world of K-pop music, television dramas, movies, food, to lifestyle. Korea has gained immense popularity in various parts of the world. In this context, this study aims to analyze the influence of the Korean Wave on Islamic culture. This journal includes a qualitative approach and content analysis to changes that occur in Islamic cultural practices and norms as a result of the Korean Wave. The result is that there are several impacts that Muslim youth have on Islamic culture through social media, Tik Tok, such as hate speech to creating content in front of the Kaaba when carrying out the pilgrimage by carrying an idol photocard and uploading it on the Tik Tok page. As a result, there was much debate about the incident, where nonK-popers gave their responses to their disapproval of this action. Many commented that loving God’s creatures should not be excessive. Others wrote that at the home of the Creator, they should not still think about worldly things.